Assessing the Capacity of Mangroves to Remove Nitrogen and Phosphorus from Coastal Shrimp Farms in Kim Son District, Ninh Binh Province - Ha, Nguyen Thi Thu; The Anh, Luu; Thi Tuyet Thu, Tran; Nhat Ha, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2, 2025)
Among the ecosystem services provided by mangrove forests, there are environmental cleaning services based on their ability to adsorb and accumulate pollutants in sediment layers as well as adsorbtion and sequestration by forest plants. In order to estimate the ability of mangrove forests to remove nitrogen (N) and phosphorus (P) from shrimp wastewater in Kim Son district, Ninh Binh province, this study conducted some laboratory analyses to confirm the NH 4 + and PO 4 3- adsorption capacity of soil and estimated the monetary value of the mangrove forests based on the emission coeficients from the farming of black tiger shrimp, white leg shrimp and the biomass incorporation coeficients of N and P by mangrove forests. Based on the amount of wastewater generated and corresponding content of N and P to be treated,  the  monetary values derived from the N   and   P  removal capacity of   the mangrove   forest s in Kim  Son district are estimated using the cost of similar treatment investment provided by other service providers. According to calculations, the amount pollutant load from shrimp farming in the coastal area of Kim Son district in 2023 is 36,953,064  kg  of N , 7,550,382  kg  of P   and  4,576,894.86 m 3   of   wastewater . The estimated results for ​​719 hectares of mangrove forests in Kim Son district in 2023 show that this area of the forests is fully capable of removing 100% of N and P found in wastewater discharged from shrimp farming activities. The value of environmental cleaning services through the ability to sequester N and P in shrimp farming wastewater of Kim Son mangrove forest is equivalent to about 16,019 billion VND/year..